Study on Current Sensorless Vector Control Method for Electric Vehicle Drive Motor - Jing Lian; Yafu Zhou; Jing Chang; Linhui Li; Xiaoyong Shen (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
With the aggravation of environment pollution and the reduction of petroleum resources, the development of electric vehicle (EV) draws more and more people’s attention. In the EV research field, that seeking for a high efficient and reliable motor control method that suits the operating conditions and characteristics of the vehicle drive motor has become one of the key techniques that need to be broken through urgently. Owing to the problems that the efficient work area is narrow and it leads to over-current phenomenon when traditional motor vector control method is applied to vehicle drive motor, this paper presents a current sensorless vector control technique for electric vehicle drive motor. According to motor speed and command torque which is gained from the speed loop control, this method directly controls the magnitude and phase angle of voltage vector to realize the orientation control of the magnetic field and then achieve the purpose of controlling the motor torque and speed. The feasibility and effectiveness of this method are verified by simulation results and bench test. Moreover, this method can not only improve the efficient work area, but also increase the reliability of motor control system. At the same time, it overcomes the dependence on the current sensor, circumvents the over-current defect caused by traditional motor vector control approach and reduces its cost. So it is a suitable and efficient control method for electric vehicle drive motor. DOI : http://dx.doi.org/10.11591/telkomnika.v12i1.3964